(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The present study determined the physicochemical parameters, saturation and unsaturation of twenty-four branded and unbranded vegetable oils sold in Sabo Market, Kaduna State by Fourier Transformed Infrared Analysis (FTIR) analysis. The branded vegetable oils were (U1 - U13), U14- U17 = unbranded vegetable oils; U18- U19 = branded palm oils; U20- U24 = unbranded palm oils. Percentage moisture content, colour, odour and rancidity were the physicochemical parameters analysed. The percentage moisture content was found to be within the ranges of 0.00 – 0. 33%. Higher moisture content was observed in samples U13 and U24. The colours and odour are in line with the standard of SON except for sample U22 which had an objectionable odour. There were records of rancidity in four (4) vegetable oils U1, U5, U16 and U17 and two (2) palm oils, U20 and U22 analyzed. The FTIR analysis indicated that there is unsaturated C-H stretching vibration peak of carbon chain at 3006 and 3648 cm-1 for the unheated samples. In comparison, peaks attributable to the presence of an aromatic group was not identified in samples U5 and U15 but was identified in H5 and H15 respectively. There was an increase in the peaks of sample U5 from 3008 and 2925 cm-1 to 3853 and 3646 cm-1 in sample H5. Heating of edible oils at smoke point changes the composition of the oil slightly by the formation of new additional compounds.